2014
DOI: 10.1002/ptr.5231
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Receptor Binding and Pharmacological Effects of N‐methyltyramine

Abstract: N-methyltyramine (NMT) is a protoalkaloid isolated from various plant species. It is assumed that NMT is an adrenergic agonist with pharmacological properties similar to other structurally related biogenic amines. Current research studies indicate that NMT is an α-adrenoreceptor antagonist, and exhibits modest inhibitory (antagonistic) activity with respect to the breakdown of fats (lipolysis). Furthermore, NMT has been shown to enhance appetite and digestion of foods through its stimulatory effects on gastrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…In conclusion, our observations in WAT, heart, muscles and plasma indicated that phenelzine did not increase the risk of lipotoxicity or cardiovascular disease in mice. The lack of increased lipid mobilization after phenelzine treatment agrees with an expected increase of tyramine content because this compound lacks strong lipolytic effect, in contrast to its derivative N‐methyltyramine (Stohs and Hartman, ). Thus, one can expect that phenelzine is not solely blocking MAO in nervous and cardiovascular systems, as it is capable of modulating carbohydrate and lipid metabolism in other tissues by interfering at least with H 2 O 2 metabolism, SSAO and PEPCK activities.…”
Section: Discussionsupporting
confidence: 73%
“…In conclusion, our observations in WAT, heart, muscles and plasma indicated that phenelzine did not increase the risk of lipotoxicity or cardiovascular disease in mice. The lack of increased lipid mobilization after phenelzine treatment agrees with an expected increase of tyramine content because this compound lacks strong lipolytic effect, in contrast to its derivative N‐methyltyramine (Stohs and Hartman, ). Thus, one can expect that phenelzine is not solely blocking MAO in nervous and cardiovascular systems, as it is capable of modulating carbohydrate and lipid metabolism in other tissues by interfering at least with H 2 O 2 metabolism, SSAO and PEPCK activities.…”
Section: Discussionsupporting
confidence: 73%
“…() also showed that, in human and rat adipocytes tyramine and N ‐methyltyramine, minor components found in bitter orange extract inhibited lipolysis in contrast to p‐ synephrine. A review of the adrenergic receptor binding and effects of N ‐methyltyramine indicate that it acts as an α‐adrenergic receptor antagonist while promoting appetite and inhibiting lipolysis, effects counter to commonly perceived ideas regarding its use in dietary supplements (Stohs and Hartman, ).…”
Section: Mechanistic Studiesmentioning
confidence: 83%
“…Hordenine stimulates norepinephrine, a hormone that mediates lipid release and can lead to body weight loss and inhibited gut movements, which contributes to decreased weight gain [33,34]. N -methyltyramine is a protoalkaloid isolated from various plant species, and it is assumed to be an adrenergic agonist with pharmacological properties similar to other structurally related biogenic amines, such as p -synephrine, p -octopamine, epinephrine, and norepinephrine, as well as ephedrine and amphetamine, which are phenylpropylamine derivatives [35]. Moreover, p -synephrine has been shown to reduce body weight in pre-clinical and clinical studies [33,36].…”
Section: Discussionmentioning
confidence: 99%